Comparing apples and pears?: a conceptual framework for understanding forms of outdoor learning through comparison of English Forest Schools and Danish udeskole. Issue 6 (17th August 2016) - Waite, Sue; Bølling, Mads; Bentsen, Peter
Abstract : Using a conceptual model focused on purposes, aims, content, pedagogy, outcomes, and barriers, we review and interpret literature on two forms of outdoor learning: Forest Schools in England and udeskole in Denmark. We examine pedagogical principles within a comparative analytical framework and consider how adopted pedagogies reflect and refract the culture in which they are embedded. Despite different national educational and cultural contexts, English Forest Schools and Danish udeskole share several commonalities within a naturalistic/progressive pedagogical tradition; differences appear in the degree of integration within national educational systems. Global calls for increased connection to nature and recent alignment of results-driven school systems in both countries influence their foundational principles, perhaps leading to greater convergence in the future. We argue that close attention to pedagogical principles are necessary to ensure better alignment of purpose and practice to elicit specific outcomes and enable comparison between different types.